INVESTIGATION OF SOME MICROBIAL AGENTS IN VAGINAL AND ENDOSERVIX SWAP SAMPLES OF 18 - 50 AGED WOMEN WITH VAGINAL DISCHARGE - Remziye İÇEN; Nezahat AKPOLAT; Nida ÖZCAN (Rojan GÜMÜŞ, 2022)
Detecting sexually transmitted infectious agents in women by traditional methods is often troublesome. This study aimed to investigate bacterial vaginosis and vaginitis agents by culture, microscopic examination, and molecular methods in women with vaginal discharge complaints. A total of 100 female patients aged 18-50 years, who applied to Dicle University Obstetrics and Gynecology outpatient clinic with the complaint of vaginal discharge, were included in the study. Gram and Giemsa staining, culture, and multiplex polymerase chain reaction (PCR) processes were performed from vaginal and endocervix samples taken with sterile swabs. Gram-stained specimens were evaluated with the Nugent score; the presence of leukocytes with polymorph nuclei, Clue-Cells, and different shaped bacteria. Culture-grown agents were identified at the species level by mass spectrometry. There was at least one microbial agent in 63% of the samples included in the study. According to Nugent scores, 27 specimens were determined positive, and 39 specimens had intermediate values for bacterial vaginosis(BV). Candida species (29%), Streptococcus agalactiae (9%), and Staphylococcus aureus (3%) grew in culture while Mycoplasma hominis (23%), Ureaplasma urealyticum (13%), Trichomonas vaginalis (9% ) and Chlamydia trachomatis (3% ) were detected by multiplex PCR. In our study, it was determined that vaginal discharge could be caused by bacterial, fungal, and parasitic microorganisms as well as bacterial vaginosis agents. It is very difficult, laborious, and necessary to determine dysbiosis and infection in the vagina which has an important microbiome. Gram staining and culture methods are insufficient for the detection of vaginal infection agents. Therefore, it would be beneficial to use molecular methods in addition.